2015
DOI: 10.1016/j.ceramint.2015.06.038
|View full text |Cite
|
Sign up to set email alerts
|

Macro-porous Ti2AlC MAX-phase ceramics by the foam replication method

Abstract: This paper describes the fabrication of porous Ti 2 AlC MAX-phase ceramics using the foam replication technique. The influence of heattreatment cycle and sintering time on phase composition, microstructure and type of defect is discussed. Compression testing indicates that strength is related to defects that are introduced during the foam replication stage, as observed by optical and electron microscopy. The manufacturing process is adapted by employing additional coating stages to produce electrically conduct… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

2
32
0

Year Published

2016
2016
2023
2023

Publication Types

Select...
5
3

Relationship

0
8

Authors

Journals

citations
Cited by 48 publications
(34 citation statements)
references
References 32 publications
(36 reference statements)
2
32
0
Order By: Relevance
“…Once the foam has been created, various shaping and consolidation techniques can be utilized to convert the wet foam into a green body. In one possible route, a “quick” setting approach such as gelcasting is used . This technology allows a versatile shaping technique suitable to many types of geometry.…”
Section: Macroporous Ceramic Structures Enabled By Colloidal Processingmentioning
confidence: 99%
See 2 more Smart Citations
“…Once the foam has been created, various shaping and consolidation techniques can be utilized to convert the wet foam into a green body. In one possible route, a “quick” setting approach such as gelcasting is used . This technology allows a versatile shaping technique suitable to many types of geometry.…”
Section: Macroporous Ceramic Structures Enabled By Colloidal Processingmentioning
confidence: 99%
“…This technique has been well studied and established using common materials such as Al 2 O 3 . The robust mechanism of this approach (see Section for more details) has also enabled the development of foams of “less common” materials, for instance; ZrB 2, MAX phases, SiC, Si 3 N 4, geopolymers, and HA …”
Section: Macroporous Ceramic Structures Enabled By Colloidal Processingmentioning
confidence: 99%
See 1 more Smart Citation
“…In the past decades, ternary carbides and nitrides ceramics known as the M n+1 AX n (MAX) phases (where n =1, 2, 3 or higher, M is an early transition metal atom, A is a group , , or elements and X is either C and/or N) have attracted much attention as promising engineering materials, due to their unique properties such as good electrical and thermal conductivity, damage tolerance, high melting point and excellent thermal shock resistance [1][2][3][4][5][6][7][8][9][10][11][12]. According to the value of layer index n, M n+1 AX n phases are labeled as 211, 312 and 413 phases for n=1, 2, 3, respectively.…”
Section: Introductionmentioning
confidence: 99%
“…So far, the majority of studies reported on these materials focus on dense components. Research on porous Ti 2 AlC and other MAX phases is rather limited . Porous MAX phases need systematic studies, because control of the porosity and pore size can be used to tailor their functional properties.…”
Section: Introductionmentioning
confidence: 99%